2015
DOI: 10.2807/1560-7917.es2015.20.25.21163
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary epidemiological assessment of MERS-CoV outbreak in South Korea, May to June 2015

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
324
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(353 citation statements)
references
References 21 publications
18
324
3
3
Order By: Relevance
“…Epidemiological characteristics of MERS cases between the two countries were also compared. The experts concluded that the adjusted case fatality ratio (adjusted by secondary infection and co-morbidity) of MERS were similar for the two countries (also similar to the results of a previous study 7 ). The Saudi Arabian experts also confirmed that MERS is transmitted mostly in droplets, reassuring airborne infections would be extremely rare.…”
Section: Conflicts Of Interestsupporting
confidence: 69%
“…Epidemiological characteristics of MERS cases between the two countries were also compared. The experts concluded that the adjusted case fatality ratio (adjusted by secondary infection and co-morbidity) of MERS were similar for the two countries (also similar to the results of a previous study 7 ). The Saudi Arabian experts also confirmed that MERS is transmitted mostly in droplets, reassuring airborne infections would be extremely rare.…”
Section: Conflicts Of Interestsupporting
confidence: 69%
“…3,4) The recent discovery of the virus in China and Korea has led to fatal disease and fear of MERS CoV epidemics. 5,6) MERS CoV is a single strand RNA virus with a relatively large genome size of 30 kb. The MERS CoV genome is composed of one large polyprotein 1ab, spike protein, envelop protein, and nucleocapsid.…”
mentioning
confidence: 99%
“…19 The largest MERS-CoV outbreak outside the Middle East occurred in South Korea in 2015, resulting in a total number of 186 cases with 36 deaths. 24 The index case, male late sixty, was returning from Bahrain after visiting multiple countries (Saudi Arabia, Qatar, and UAE). The patient developed symptoms to which he attended various hospitals, resulting in an outbreak affecting five health care facilities escalating to involve 67 more by June 19, 2015.…”
Section: Major Outbreaks and Clustersmentioning
confidence: 99%